Secondary dengue virus infection is associated with endothelial activation and hypotension in an outpatient cohort from the Philippines - Jiayi Yang; Hridesh Mishra; Michelle Ngai; Vanessa Tran; Maria Salome Siose Painaga; James Yared Gaite; Ashley Roberts; Andrea L. Conroy; Kevin C. Kain; Michael T. Hawkes (Infectious Diseases, 2026)

Inventory Measurement Rates Lag in Wilderness Areas Across the Western USA - David L. R. Affleck; George C. Gaines; Cici Conroy; Gianna Santino; Andrew J. Larson (Forest Science, 2026)

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Human presence shifts the landscape of fear for a free‐living mammal - Chelsea A. Ortiz‐Jimenez; Sophie Z. Conroy; Erin S. Person; Jasper DeCuir; Gabriella E. C. Gall; Andrew Sih; Jennifer E. Smith (Ecology, 2025)
Humans may play a key role in providing small prey mammals spatial and temporal refuge from predators, but few studies have captured the heterogeneity of these effects across space and time. Global COVID‐19 lockdown restrictions offered a unique opportunity to investigate how a sudden change in human presence in a semi‐urban park impacted wildlife. Here, we quantify how changes in the spatial distributions of humans and natural predators influenced the landscape of fear for the California ground squirrel ( Otospermophilus beecheyi ) in a COVID‐19 pandemic (2020) and non‐COVID (2019) year. We used a structural equation modeling approach to explore the direct and indirect effects of human presence, predator presence, and habitat features on foraging that reflected fear responses (e.g., giving‐up densities [GUDs], number of foragers, and average food intake rate while at food patches). In 2019, humans and dogs had moderate effects on GUDs; squirrels were less fearful (lower GUDs) in areas frequently visited by humans and dogs, but the effects of raptors were weak. In contrast, in 2020, the effects of humans and dogs on GUDs were weak; squirrels were more fearful of high raptor activity, open sky, and ground cover. In both years, squirrels farthest from refuge were the most risk‐averse. Overall, our analyses revealed an increase in perceived risk from natural predators in 2020 associated with a change in the concentration of human presence. Thus, risk‐sensitive foraging was dynamic across space and time, depending on a complex interplay among human and dog activity, natural predators, and microhabitat features. Our findings elucidate the myriad ways humans directly and indirectly influence animal perception of safety and danger.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A decision methodology for site-level ecosystem accounting - Courtney E. Gorman; Francesco Martini; Kathleen Conroy; Emma King; Reiss Mcleod; Carl Obst; Jane C. Stout; Ian Donohue; Yvonne M. Buckley (Journal of Environmental Management, 2024)

Isolation, small population size, and management influence inbreeding and reduced genetic variation in K’gari dingoes - Susan M. Miller; Linda Behrendorff; Benjamin L. Allen; Rose L. Andrew; Guy Ballard; J. William O. Ballard; Kylie M. Cairns; Gabriel C. Conroy; Peter J. S. Fleming; Catherine E. Grueber; Jane Oakey; Deane A. Smith; et al. (Conservation Genetics, 2024)
Small island populations are vulnerable to genetic decline via demographic and environmental stochasticity. In the absence of immigration, founder effects, inbreeding and genetic drift are likely to contribute to local extinction risk. Management actions may also have a greater impact on small, closed populations. The demographic and social characteristics of a species can, however, delay the impact of threats. K’gari, a ~ 1 660 km 2 island off the Australian east coast and UNESCO World Heritage Site (Fraser Island 1842–2023), supports an isolated population of approximately 70–200 dingoes that represent an ideal opportunity to explore the small island paradigm. To examine temporal and spatial patterns of genetic diversity in this population we analysed single nucleotide polymorphism (SNP) genotype data (72 454 SNPS) for 112 K’gari dingoes collected over a 25-year period (1996 to 2020). Genetic diversity was lower in K’gari dingoes than mainland dingoes at the earliest time point in our study and declined significantly following a management cull in 2001. We did not find any spatial genetic patterns on the island, suggesting high levels of genetic connectivity between socially discrete packs. This connectivity, combined with the social structure and behaviour of dingoes, may act in concert to buffer the population from the impacts of genetic drift in the short term. Nevertheless, a general decline in genetic variation via inbreeding and drift has occurred over the past 20 years which we suggest should be considered in any future management planning for the population. Monitoring patterns of genetic variation, together with a clearer understanding of the social ecology of K’gari dingoes, will aid in the development of measurable genetic targets set over ecologically meaningful timelines, and help ensure continued survival of this culturally important population.

Omnivorous summer feeding by juvenile Antarctic krill in coastal waters - John A. Conroy; Deborah K. Steinberg; Schuyler C. Nardelli; Oscar Schofield (Limnology and Oceanography, 2024)
The Antarctic krill Euphausia superba is often considered an herbivore but is notable for its trophic flexibility, which includes feeding on protistan and metazoan zooplankton. Characterizing krill trophic position (TP) is important for understanding carbon and energy flow from phytoplankton to vertebrate predators and to the deep ocean, especially as plankton composition is sensitive to changing climate. We used repeated field sampling and experiments to study feeding by juvenile krill during three austral summers in waters near Palmer Station, Antarctica. Our approach was to combine seasonal carbon budgets, gut fluorescence measurements, imaging flow cytometry, and compound‐specific isotope analysis of amino acids. Field measurements coupled to experimentally derived grazing functional response curves suggest that phytoplankton grazing alone was insufficient to support the growth and basal metabolism of juvenile krill. Phytoplankton consumption by juvenile krill was limited due to inefficient feeding on nanoplankton (2–20 μ m), which constituted the majority of autotrophic prey. Mean krill TP and the metazoan dietary fraction increased in years with higher mesozooplankton biomass, which was not coupled to phytoplankton biomass. Comparing TP estimates using δ 15 N of different amino acids indicated a substantial and consistent food‐web contribution from heterotrophic protists. Phytoplankton, metazoans, and heterotrophic protists all were important contributors to a diverse krill diet that changed substantially among years. Juvenile krill fed mostly on heterotrophic prey during summer near Palmer Station, and this food web complexity should be considered more broadly throughout the changing Southern Ocean.

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Pseudomonas umsongensis GO16 as a platform for the in vivo synthesis of short and medium chain length polyhydroxyalkanoate blends - Federico Cerrone; Binbin Zhou; Agathe Mouren; Luc Avérous; Stephen Conroy; Jeremy C. Simpson; Kevin E. O'Connor; Tanja Narancic (Bioresource Technology, 2023)

Disparities in cause-specific mortality by race and sex among bladder cancer patients from the SEER database - Timothy D. Shu; Fredrick R. Schumacher; Britt Conroy; Lee Ponsky; Amr Mahran; Laura Bukavina; Adam Calaway; Sarah C. Markt (Cancer Causes & Control, 2023)

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Corrections to: Interpreting lacustrine bulk sediment δ15N values using metagenomics in a tropical hypersaline lake system - Mingfei Chen; Jessica L. Conroy; Robert A. Sanford; Joanne C. Chee-Sanford; Lynn M. Connor (Journal of Paleolimnology, 2022)

Krill availability in adjacent Adélie and gentoo penguin foraging regions near Palmer Station, Antarctica - Schuyler C. Nardelli; Megan A. Cimino; John A. Conroy; William R. Fraser; Deborah K. Steinberg; Oscar Schofield (Limnology and Oceanography, 2021)
The Palmer Deep canyon along the West Antarctic Peninsula is a biological hotspot with abundant phytoplankton and krill supporting Adélie and gentoo penguin rookeries at the canyon head. Nearshore studies have focused on physical mechanisms driving primary production and penguin foraging, but less is known about finer‐scale krill distribution and density. We designed two acoustic survey grids paired with conductivity–temperature–depth profiles within adjacent Adélie and gentoo penguin foraging regions near Palmer Station, Antarctica. The grids were sampled from January to March 2019 to assess variability in krill availability and associations with oceanographic properties. Krill density was similar in the two regions, but krill swarms were longer and larger in the gentoo foraging region, which was also less stratified and had lower chlorophyll concentrations. In the inshore zone near penguin colonies, depth‐integrated krill density increased from summer to autumn (January–March) independent of chlorophyll concentration, suggesting a life history‐driven adult krill migration rather than a resource‐driven biomass increase. The daytime depth of krill biomass deepened through the summer and became decoupled from the chlorophyll maximum in March as diel vertical migration magnitude likely increased. Penguins near Palmer Station did not appear to be limited by krill availability during our study, and regional differences in krill depth match the foraging behaviors of the two penguin species. Understanding fine‐scale physical forcing and ecological interactions in coastal Antarctic hotspots is critical for predicting how environmental change will impact these ecosystems.

Interpreting lacustrine bulk sediment δ15N values using metagenomics in a tropical hypersaline lake system - Mingfei Chen; Jessica L. Conroy; Robert A. Sanford; Joanne C. Chee-Sanford; Lynn M. Connor (Journal of Paleolimnology, 2021)

Last glacial maximum ecology and climate from terrestrial gastropod assemblages in Peoria loess, western Kentucky - David A. Grimley; Ronald C. Counts; Jessica L. Conroy; Hong Wang; Sarah N. Dendy; Catherine B. Nield (Journal of Quaternary Science, 2020)
The Rocks loess section, in unglaciated western Kentucky, provides a high‐resolution environmental record during the last glacial maximum onset. The Peoria Silt (9 m thick) contains 26 terrestrial gastropod species, with up to 15 species within a single 5 cm interval. Thirteen radiocarbon ages, using shells or charcoal, range between 30 and 24.5 cal ka; younger loess has been leached or eroded. Stratigraphic shifts in gastropod assemblages imply significant cooling, particularly ~27 cal ka, as solar insolation was decreasing and the southern Laurentide Ice Sheet rapidly advancing. Midwestern to southern species (e.g. Anguispira kochi , Gastrocopta pentodon , Hawaii miniscula , Helicodiscus parallelus , Vallonia perspectiva ) occur only in the lowermost Peoria Silt (~30–27 cal ka). In contrast, cold‐tolerant species ( Columella alticola , Vertigo modesta, Vallonia gracilicosta) occur only in full glacial Peoria Silt (27–24.5 cal ka). Inferred mean July temperatures, from mutual climatic range methods, range from ~23 °C at 30 cal ka, cooling to ~18 °C by 26 cal ka; about 3–8 °C cooler than today (~26 °C). Superimposed on this cooling trend are multi‐centennial variations in detrital carbonate, fossil shell concentrations, palaeotemperature estimates, and oxygen isotope values ( Vertigo , Discus, Helicodiscus ). The finer‐scale variations imply relatively synchronous fluctuations in glacial sediment supply, loess sedimentation, and climate.

Gut microbial diversity across a contact zone for California voles: Implications for lineage divergence of hosts and mitonuclear mismatch in the assembly of the mammalian gut microbiome - Dana Lin; Eileen A. Lacey; Bryan H. Bach; Ke Bi; Christopher J. Conroy; Anton Suvorov; Rauri C. K. Bowie (Molecular Ecology, 2020)
Gut microbial diversity is thought to reflect the co‐evolution of microbes and their hosts as well as current host‐specific attributes such as genetic background and environmental setting. To explore interactions among these parameters, we characterized variation in gut microbiome composition of California voles ( Microtus californicus ) across a contact zone between two recently diverged lineages of this species. Because this contact zone contains individuals with mismatched mitochondrial‐nuclear genomes (cybrids), it provides an important opportunity to explore how different components of the genotype contribute to gut microbial diversity. Analyses of bacterial 16S rRNA sequences and joint species distribution modelling revealed that host genotypes and genetic differentiation among host populations together explained more than 50% of microbial community variation across our sampling transect. The ranked importance (most to least) of factors contributing to gut microbial diversity in our study populations were: genome‐wide population differentiation, local environmental conditions, and host genotypes. However, differences in microbial communities among vole populations (β‐diversity) did not follow patterns of lineage divergence (i.e., phylosymbiosis). Instead, among‐population variation was best explained by the spatial distribution of hosts, as expected if the environment is a primary source of gut microbial diversity (i.e., dispersal limitation hypothesis). Across the contact zone, several bacterial taxa differed in relative abundance between the two parental lineages as well as among individuals with mismatched mitochondrial and nuclear genomes. Thus, genetic divergence among host lineages and mitonuclear genomic mismatches may also contribute to microbial diversity by altering interactions between host genomes and gut microbiota (i.e., hologenome speciation hypothesis).

Population variation in the intensity of fruit infestation and pre-dispersal seed predation in Yucca schidigera (Asparagaceae) by its obligate pollinator - Leonardo De la Rosa-Conroy; Maria C. Arteaga; Stephen H. Bullock; Luis E. Eguiarte; Rafael Bello-Bedoy (Plant Ecology, 2019)

Staphylococcus aureus heme and siderophore-iron acquisition pathways - Brigid S. Conroy; Jason C. Grigg; Maxim Kolesnikov; L. Daniela Morales; Michael E. P. Murphy (BioMetals, 2019)

Genetic diversity and structure of the threatened striped legless lizard, Delma impar: management implications for the species and a translocated population - Codie Murphy; Scott Burnett; Gabriel C. Conroy; Brett W. A. Howland; Robert W. Lamont; Joanna Sumner; Steven M. Ogbourne (Conservation Genetics, 2019)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

αv integrins: key regulators of tissue fibrosis - Kylie P. Conroy; Laura J. Kitto; Neil C. Henderson (Cell and Tissue Research, 2016)

Nitrogen sources and net growth efficiency of zooplankton in three A mazon River plume food webs - Natalie Loick‐Wilde; Sarah C. Weber; Brandon J. Conroy; Douglas G. Capone; Victoria J. Coles; Patricia M. Medeiros; Deborah K. Steinberg; Joseph P. Montoya (Limnology and Oceanography, 2016)

Antagomirs targeting microRNA-134 increase hippocampal pyramidal neuron spine volume in vivo and protect against pilocarpine-induced status epilepticus - Eva M. Jimenez-Mateos; Tobias Engel; Paula Merino-Serrais; Isabel Fernaud-Espinosa; Natalia Rodriguez-Alvarez; James Reynolds; Cristina R. Reschke; Ronan M. Conroy; Ross C. McKiernan; Javier deFelipe; David C. Henshall (Brain Structure and Function, 2015)

Population genetics of Philotheca sporadica (Rutaceae) to advise an offset translocation program - Alison Shapcott; Robert W. Lamont; Katie M. O’Connor; Heather James; Gabriel C. Conroy (Conservation Genetics, 2015)

Chemotherapy-induced amenorrhea: a prospective study of brain activation changes and neurocognitive correlates - Susan K. Conroy; Brenna C. McDonald; Tim A. Ahles; John D. West; Andrew J. Saykin (Brain Imaging and Behavior, 2013)

Cryptic genetic diversity in Rattus of the San Francisco Bay region, California - Chris J. Conroy; Kevin C. Rowe; Karen M. C. Rowe; Pauline L. Kamath; Ken P. Aplin; Lucia Hui; David K. James; Craig Moritz; James L. Patton (Biological Invasions, 2013)

Size increase in high elevation ground squirrels over the last century - Lindsey M. Eastman; Toni Lyn Morelli; Kevin C. Rowe; Chris J. Conroy; Craig Moritz (Global Change Biology, 2012)
There is increasing evidence for morphological change in response to recent environmental change, but how this relates to fluctuations in geographic range remains unclear. We measured museum specimens from two time periods (1902–1950 and 2000–2008) that vary significantly in climate to assess if and how two high elevation contracting species of ground squirrels in the Sierra Nevada of California, Belding's ground squirrel ( Urocitellus beldingi ) and the golden‐mantled ground squirrel ( Callospermophilus lateralis ), and one lower elevation, stable species, the California ground squirrel ( Otospermophilus beecheyi ), have responded morphologically to changes over the last century. We measured skull length (condylobasal length), an ontogenetically more labile trait highly correlated with body size, and maxillary toothrow length, a more developmentally constrained trait predictive of skull shape. C. lateralis and U. beldingi , both obligate hibernators, have increased in body size, but have not changed in shape. In contrast, O. beecheyi , which only hibernates in parts of its range, has shown no significant change in either morphometric trait. The increase in body size in the higher elevation species, hypothesized to be a plastic effect due to a longer growing season and thus prolonged food availability, opposes the expected direction of selection for decreased body size under chronic warming. Our study supports that population contraction is related to physiological rather than nutritional constraints.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Detection heterogeneity in underwater visual‐census data - M. A. MacNeil; N. A. J. Graham; M. J. Conroy; C. J. Fonnesbeck; N. V. C. Polunin; S. P. Rushton; P. Chabanet; T. R. McClanahan (Journal of Fish Biology, 2008)
This study shows how capture–mark–recapture (CMR) models can provide robust estimates of detection heterogeneity (sources of bias) in underwater visual‐census data. Detection biases among observers and fish family groups were consistent between fished and unfished reef sites in Kenya, even when the overall level of detection declined between locations. Species characteristics were the greatest source of detection heterogeneity and large, highly mobile species were found to have lower probabilities of detection than smaller, site‐attached species. Fish family and functional‐group detectability were also found to be lower at fished locations, probably due to differences in local abundance. Because robust CMR models deal explicitly with sampling where not all species are detected, their use is encouraged for studies addressing reef‐fish community dynamics.

Phylogeography of a post‐glacial colonizer: Microtus longicaudus (Rodentia: Muridae) - C. J. Conroy; J. A. Cook (Molecular Ecology, 2000)
The molecular phylogeography of Microtus longicaudus was investigated with DNA sequences of the mitochondrial cytochrome b gene. We used phylogenetic and pairwise distance methods to reconstruct the history of the species with particular emphasis on the Pacific Northwest. Genetic variation across the species was consistent with vicariant events during the Pleistocene and subsequent northern postglacial expansion following the receding Laurentide and Cordilleran ice sheets. The largest break (> 6% uncorrected sequence divergence) was found to exist between populations found southeast of the Colorado River (eastern Arizona, Colorado, Wyoming and New Mexico) and all other western populations. Other well‐supported subclades were composed of samples from: (i) the islands and north coast of southeast Alaska; (ii) eastern Alaska, British Columbia, Washington and Oregon; and (iii) northern California, Idaho and Montana. Within subclades, divergence was low. Our results suggest that the close relationships among haplotypes within northern subclades are a result of recent colonization, whereas higher among‐subclade divergence is caused by genetic differentiation during prolonged periods of isolation, possibly as a result of mid‐Pleistocene climatic events.

Imperata management strategies used in smallholder rubber-based farming systems - H. Bagnall-Oakeley; C. Conroy; A. Faiz; A. Gunawan; A. Gouyon; E. Penot; S. Liangsutthissagon; H. D. Nguyen; C. Anwar (Agroforestry Systems, 1996)

Eucalyptus sales by small farmers in eastern Gujarat - C. Conroy (Agroforestry Systems, 1993)